The Use of Cornel Note-Taking Method in Improving Students Reading Retention at SMPN 1 Segeri. - Rafiqa Salwa Patty Salwa; Abdullah; Munir (International Journal of Language, Education, and Literature, 2025)
This study, The Use of Cornell Note-taking Method in Improving Reading Retention. The study aimed to determine (1)To what extent does the use of Cornell note-taking improve reading retention of the eighth-grade students of SMPN 1 Segeri (2) How do the students perceive the use of the Cornell note-taking method in improving reading retention at SMP Negeri 1 Segeri This study used a mixed-methods approach with an explanatory design. The population of this study was the students of SMP Negeri 1 Segeri. The samples of this study were the VIII Hasanudin class, consisting of 23 students as the experimental class, and the VIII Syekh Yusuf class, consisting of 19 students as the control class. The researcher used multiple-choice tests and interviews as the research instruments. The results of this study showed that (1) The use of cornell note-taking method can improve the reading retention of eighth-grade students of SMP Negeri 1 Segeri. (2) Students' perceptions of using Cornell Note-taking method in improve reading retention had a positive perception. This illustrates that the use of Cornell note-taking method can improve the reading retention of eighth-grade students of SMP Negeri 1 Segeri.